The Effectiveness of Weaving Activities in Improving Fine Motoric in Group B Children TK Aisyiyah Bustanul Athfal 05 Mustafa Street No. 3 Medan - Regita Indah Cahyani (Yayasan Rahmat Islamiyah, 2023)
Â In improving the fine motoric quality of Early Childhood, teachers must have high creativity in conveying learning by using activities that make children motivated and eager to learn. One of them is with weaving activities which have the aim of improving fine motor skills in early childhood. This study uses qualitative methods and is descriptive with data collection techniques by observation, interviews, purpose of this study was to determine the development of children's fine motor skills through weaving mats and mangoes in kindergarten. Aisyiyah Bustanul Athfal 05 Medan. The results of the study show that children's fine motor development can develop through this weaving activity. Although still need guidance and direction from the teacher. And it is hoped that kindergarten teachers After this research is carried out, it is necessary to have an in-depth teaching intensity for children's motor development in the school. One of them is by using weaving activities and not sticking to the diary at school.